Carotenoid Assessments and Antioxidant Activities from Flower Petals - Ratananikom, Khakhanang; Nasinporm, Nipa; Pongjongmit, Tanitpan (HAYATI Journal of Biosciences, 2021)
The objectives of this study were to evaluate carotenoid pigment profile and the antioxidant activity from 14 commonly grown flowers in Thailand. The result found that orange marigold showed the highest total carotenoid content at as 2,209±75.58 µg/g, followed by deep yellow chrysanthemum at 551.27±47.72 µg/g (P